Evaluation of neutropenia secondary to mycophenolate mofetil associated with valganciclovir in liver transplant patients - Alejandro Ferrer-Machín; Martín Vera-Cabrera; Inmaculada Plasencia-García; Antonia Moreno-García; Lina I. Pérez-Méndez; Javier Merino-Alonso (Elsevier, 2021)
Objective: Immunosuppressive drugs are necessary to avoid or reduce the risk of rejection of transplanted organs. The immunosuppression generated may result in these patients needing antibiotics and antivirals to be prescribed to them in conjunction with their immunosuppressants to avoid the risk of infection. This has generated an increase in neutropenia in patients treated with mycophenolate mofetil in combination with valganciclovir. The purpose of this study is to estimate the risk of neutropenia attributable to combination treatment of mycophenolate mofetil with valganciclovir in patients with a transplanted liver. Method: This is a retrospective cohort study. It included patients who received a liver transplant between 2012 and 2017 and who were treated with mycophenolate mofetil or with a combination of mycophenolate mofetil and valganciclovir. Minimum follow-up was 100 days posttransplantation. Children under 16 years of age and patients who died during follow-up were excluded. Binary logistic regression analysis was used to determine the association of neutropenia with sex, age, diabetes, creatinine at baseline and at discharge, and concomitant treatment of mycophenolate mofetil with valganciclovir. Relative risk and 95% CI were calculated using logistic regression coefficients. Results: 144 patients were analyzed, 87 were treated with mycophenolate mofetil and 57 received mycophenolate mofetil and valganciclovir together. An overall risk of neutropenia of 37% [95% CI (29- 45)] was observed. The risk was significantly higher in patients who received the combination of mycophenolate mofetil and valganciclovir (56%) than in those treated with mycophenolate mofetil alone (24%), p = 0.001. Binarylogistic-regression analysis revealed that concomitant use of mycophenolate mofetil with valganciclovir was associated with an increased risk of neutropenia: Relative risk = 4.97, 95% CI [2.25-11.00]. Conclusions: Our study shows that concomitant use of mycophenolate mofetil and valganciclovir increases the risk of neutropenia in patients with a transplanted liver.